Review of the Application of Nanocellulose in Food - Jiachuan Yang; Peijin Guo (Journal of Natural Fibers)
Nanocellulose, an emerging nanomaterial with high strength, tunable surface chemistry, and biocompatibility, enables diverse applications in food engineering. Its non-cytotoxic nature supports use in three key areas: food additives, functional ingredient carriers, and biodegradable packaging – the most advanced application leveraging its barrier properties. However, safety concerns persist, particularly regarding nanoparticle penetration through biological barriers (e.g. intestinal epithelium), despite preliminary studies on cytotoxicity and biodynamics. This review synthesizes: (1) extraction methods (mechanical, chemical, enzymatic) for nanocellulose production; (2) chemical modifications (carboxylation, TEMPO-oxidation) to enhance functionality; (3) food-specific applications, including active packaging (antimicrobial/antioxidant films), texture modifiers, and edible coatings. Current challenges center on reconciling scalability, safety validation, and regulatory gaps. Future directions emphasize green synthesis (agricultural waste valorization) and smart delivery systems for bioactive compounds. By addressing these aspects, nanocellulose can drive sustainable innovation in food technology, balancing performance with health and environmental priorities.